Crystallization behavior of air-plasma-sprayed ytterbium-silicate-based environmental barrier coatings. Issue 6 (June 2021) - Garcia, Eugenio; Garces, Hector F.; Turcer, Laura R.; Bale, Hrishikesh; Padture, Nitin P.; Sampath, Sanjay
Abstract: A combination of characterization techniques has been used to provide new understanding of the complex crystallization behavior of as-sprayed amorphous Yb2 Si2 O7 -based air-plasma-sprayed environmental barrier coatings (EBCs). During crystallization heat-treatment, initially a mixture of metastable α-Yb2 Si2 O7 and X1-Yb2 SiO5 phases form, along with stable β-Yb2 Si2 O7 and X2-Yb2 SiO5 phases. Eventually the metastable phases transform to the stable β-Yb2 Si2 O7 (major) and X2-Yb2 SiO5 (minor) phases. The significant volume expansion associated with these transformations partially contributes towards the anomalous expansion measured in these EBCs after crystallization, but it does not account for all the measured expansion. In this context, in similar EBCs, it is also observed that the porosity increases upon crystallization heat-treatment, primarily in the form of thin, interconnected pores, which also contributes to the measured anomalous expansion. Based on this understanding, guidelines are provided for 'near-net-shape' crystallization of phase-pure, dense β-Yb2 Si2 O7 EBCs that are free of vertical cracks.